Profibrillatory Structural and Functional Properties of the Atrial-Pulmonary Junction in the Absence of Remodeling - Gottlieb, Lisa A.; Belterman, Charly; van Amersfoorth, Shirley; Loyer, Virginie; Constantin, Marion; Hocini, Mélèze; Dekker, Lukas R. C.; Coronel, Ruben (Frontiers in Physiology, 2021)
Background: Sole pulmonary vein (PV) isolation by ablation therapy prevents atrial fibrillation (AF) in patients with short episodes of AF and without co-morbidities. Because incomplete PV isolation can be curative, we tested the hypothesis that the PV in absence of remodeling and of co-morbidities contain structural and functional properties that are proarrhythmic for AF initiation by reentry. Methods: We performed percutaneous transvenous in vivo endocardial electrophysiological studies and quantitative histological analysis of PV from healthy sheep. Results: The proximal PV contained more myocytes than distal PV and a higher percentage of collagen and fat tissue relative to myocytes than the left atrium. Local fractionated electrograms occurred in both distal and proximal PV, but a large local activation (> 0.75 mV) was more often present in the proximal than distal PV (86% vs. 50% of electrograms, respectively, p = 0.017). Atrial arrhythmias (run of premature atrial complexes) occurred more often following premature stimulation in proximal than in distal PV (p = 0.004). The diastolic stimulation threshold was higher in proximal than distal PV (0.7 [0.3] vs. 0.4 [0.2] mA, (median [interquartile range]), p = 0.004). The refractory period was shorter in proximal than distal PV (170 [50] vs. 248 [52] ms, p < 0.001). A linear relation existed between the gradient in refractoriness (distal–proximal) and atrial arrhythmia inducibility in the proximal PV. Conclusion: The structural and functional properties of the native atrial-PV junction differ from those of the distal PV. Atrial arrhythmias in the absence of arrhythmia-induced remodeling are caused by reentry in the atrial-PV junction. Ablative treatment of early paroxysmal AF may be limited to inhibition of reentry, rather than complete isolation of focal arrhythmia.